If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6-4x=26
We simplify the equation to the form, which is simple to understand
-6-4x=26
We move all terms containing x to the left and all other terms to the right.
-4x=+26+6
We simplify left and right side of the equation.
-4x=+32
We divide both sides of the equation by -4 to get x.
x=-8
| 6k-5k+8k-4k= | | -x^3-6=-7 | | 2(5-2z)-2(4z+6)=z-8 | | -2(7k+4)+9=32 | | (-8)x(6)= | | (j-3)j+4+j=196 | | 16x+11x=y | | x^2=16-28 | | 7v+6-3v=2 | | 5x+2=7x-48 | | 5(x+6x)=40(3-4x) | | 3(2r+1)=26+6r | | 10-20x+x=9x-33 | | -12/7+x=48/7 | | (5)x(-2)= | | 20x+x=180 | | 2b+11=-15 | | -8=-10-2 | | 3x^2+4=2x^2+4 | | -7-(3n+6)=-4-6n | | 15-20y+14y=15-35y | | 2(y+8)=32 | | -5(8n+6)+8(-3-n)=-54 | | 211=11x+13(19-x) | | 4+5b-5b=4 | | 35=7b | | 8(1y-5)=6y-18 | | 7x-19=-54 | | -2(4+7m)+6(4m-1)=-4 | | -7+12=-45 | | 2b-6=x | | 97=-7(1-7b)+3b |